2016
DOI: 10.1002/jmv.24448
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phylogenetic analysis of HTLV‐1 in a segregated population in Iran

Abstract: Human T-lymphotropic virus type 1 (HTLV-1) infection is an important health issue that affects a variety of endemic areas. The Khorasan province, mainly its capital Mashhad in northeastern Iran, was reported to be as one of these endemic regions. Torbat-e Heydarieh, a large city Southwest border to Mashhad with a segregated population was investigated for the prevalence and associated risk factors of HTLV-1 infection in 400 randomly selected individuals. Blood samples were tested for the presence of HTLV-1 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…[16][17][18] However, the prevalence of HTLV-1 was 10 times lower than North and Razavi Khorasan provinces (0.3% vs. 2-3%), 11 and even 4 times lower than a segregated population in this region close to South Khorasan. 12 On the other hand, in other studies on subjects at risk of these viruses in northeastern Iran, 1,[19][20][21] the sero-prevalence of blood-borne oncogenic viruses (HCV, HBV, HTLV-1 and KSHV infections) was reported to be considerably higher than our study. With respect to the present study, it is more likely that the source of HTLV-1 infection in Iran, as an archetypic virus, is in Razavi Khorasan, Neyshabour or Mashhad.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…[16][17][18] However, the prevalence of HTLV-1 was 10 times lower than North and Razavi Khorasan provinces (0.3% vs. 2-3%), 11 and even 4 times lower than a segregated population in this region close to South Khorasan. 12 On the other hand, in other studies on subjects at risk of these viruses in northeastern Iran, 1,[19][20][21] the sero-prevalence of blood-borne oncogenic viruses (HCV, HBV, HTLV-1 and KSHV infections) was reported to be considerably higher than our study. With respect to the present study, it is more likely that the source of HTLV-1 infection in Iran, as an archetypic virus, is in Razavi Khorasan, Neyshabour or Mashhad.…”
Section: Discussioncontrasting
confidence: 81%
“…11 Even a segregated population in the Razavi Khorasan, close to South Khorasan, is endemic (1.25%) for this virus. 12 Given the importance of global growth of HTLV-1 along with the danger of its co-infections with other common blood-borne oncogenic viruses, it could provide new insights into the world of microbial pathogenicity. Therefore, in this study, the incidence of HTLV-1 infection and co-infections of BBVs in Birjand, Iran's eastern border, were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that HTLV-1 prevalence among blood donors of Babol was 0.2%. This finding showed that the rate of HTLV-1 infection in blood donors of Babol is lower than infection rate in endemic areas, such as Mashhad, Neyshbour, Sabzevar, and other non-endemic provinces, such as West Azarbaijan and Charmahal-Bakhtiari (6,(12)(13)(14)(15). However, the current results were almost similar to the HTLV-1 prevalence in blood donors of provinces, such as Alborz, Ilam, and Hormozgan (8).…”
Section: Discussionmentioning
confidence: 93%
“…To the best of the best of our knowledge, no previous phylogenetic studies were conducted in Tehran and Urmia. Previous studies in Iran, such as Sabzevar, Torbat‐e Heydarieh, and Mashhad revealed that HTLV‐1 genotype belongs to the subtype a and the related subgroup was only reported in a recent study in Mashhad . Studied populations in these surveys were varied; studies about people born in Mashhad show that the HTLV‐1 genotype belongs to the cosmopolitan clade .…”
Section: Discussionmentioning
confidence: 99%